Новое содержание правозащитной функции современного украинского государства - Аракелян, Мінас Рамзесович; Аракелян, Минас Рамзесович; Arakeljan, Minas (Аракелян М. Р. Новое содержание правозащитной функции современного украинского государства / М. Р. Аракелян // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. - Вип. 67. - С. 32-39., 2012)
The article discussed the problem of transforming of the content of human rights function of the modern state. Particular attention is paid to the implementation of human rights function of the modern Ukrainian state in the context of the legal reforms that were traversed in the country.
Аракелян М. Р. Новое содержание правозащитной функции современного украинского государства / М. Р. Аракелян // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. - Вип. 67. - С. 32-39.
Keywords: правозащитная функция; современное украинское государство; правовое государство; функции государства; правозахисна функція; сучасна українська держава; правова держава; функції держави; advocacy function; modern Ukrainian state; constitutional state; защита прав и свобод человека; protection of human rights and freedoms; захист прав людини та громадянина; state functions